The labor unionism of 1946 - Öztürk, Osman. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2006., 2006)
During the transition to a multi-party system in Turkey during 1946, the prohibition of founding societies “based on class” was lifted. Thus, the way was open to unionist organizations. At this turning point of the Republic’s history, socialists had been forced to work underground to establish legal parties and take their place in the political arena. The Türkiye Sosyalist Partisi (TSP), the Turkish Socialist Party, and the Türkiye Sosyalist Emekçi ve Köylü Partisi (TSEKP), the Turkish Socialist Workers and Peasants Party, were founded and started to organize unions. Although the two parties adopted different methods in organization, this unionist experience conducted by the supporters of TSP and TSEKP is known as “Labor Unionism of 1946” in the Turkish unionist literature. Both socialist parties and the unions that were founded by their supporters were closed on December 16, 1946 by the Martial Law Command. Labor Unionism of 1946, even though it lasted only a short period, was organized in a noticeable and speedy fashion among the working class. The prohibition of the Labor Unionism of 1946 which was essentially of a socialist worldview based on class unionism opened the way to a different type of unionism that is known as the “Labor Unionism of 1947” in Turkey. The Labor Unionism of 1946 and the developments that took place around it, is an early example of indicating how a multi-party system would take shape in Turkey and provide clues for the understanding of Turkish politics and the history of the labor class.
Keywords: Working class -- Turkey.; Labor unions -- Turkey.